Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T18:45:50+01:00
X/5 -y/4=0
x/2-y/16=5,5

x/5 =y/4
-y/16=5,5 - x/2 */2

x/5 =y/4 */20
-y/8=11 - x

4x=5y
-x=-y/8 -11 */-1

5y=4x
x=y/8 + 11

5y=4* (y/8 + 11)
x=y/8 + 11

5y= y/2 + 44 */2
x=y/8 + 11

10y=y + 88
x=y/8 + 11

10y-y=88
x=y/8 + 11

9y=88 :/9
x=y/8 + 11 */8

y=88/9
8x=y+ 88

y=88/9
8x=88/9 + 88 */9

y=88/9
72x=88 +792 :/72

y=88/9
x=1 2/9 + 11

y=9 7/9 (dziewięć i siedem dziewiątych)
x=12 2/9(dwanaście i dwie dziewiąte)

XD skonczone!!!!!




1 5 1